Extracellular Signals of a Human Epithelial Colorectal Adenocarcinoma (Caco-2) Cell Line Facilitate the Penetration of Pseudomonas aeruginosa PAO1 Strain through the Mucin Layer - Hayashi, Naoki; Yokotani, Atsushi; Yamamoto, Masami; Kososhi, Mariko; Morita, Mayu; Fukunishi, Chiaki; Nishizawa, Nagisa; Gotoh, Naomasa (Frontiers in Cellular and Infection Microbiology, 2017)
Pseudomonas aeruginosa can penetrate the layer of mucus formed by host intestinal epithelial cells, often resulting in sepsis in immunocompromised patients. We have previously demonstrated that P. aeruginosa can penetrate the mucin layer by flagellar motility and the degradation of the mucin layer. However, it remains unclear how P. aeruginosa initially recognizes epithelial cells. Using the human epithelial colorectal adenocarcinoma (Caco-2) cell line, we investigated extracellular signaling that could facilitate the penetration of P. aeruginosa through the mucin layer. The supernatant from Caco-2 cell cultures increased penetration of P. aeruginosa through an artificial mucin layer. The Caco-2 cell supernatant increased bacterial flagella-dependent swarming motility, but it did not influence P. aeruginosa growth or protease activity. Filtering of the Caco-2 cell supernatant indicated that proteins weighing <10 kDa increased mucin penetration, swarming motility, and, based on a tethered cell assay, induced acceleration of the flagellar filament rotational rate. Furthermore, a capillary assay showed that <10 kDa proteins in the Caco-2 cell supernatant attracted P. aeruginosa cells. Finally, we identified that growth-regulated oncogene-alpha (GRO-alpha secreted by Caco-2 cells was a factor facilitating flagellar filament rotation and swarming motility, although it did not attract the bacteria. We conclude that penetration of the mucin layer by P. aeruginosa is facilitated by small proteins (<10 kDa) secreted by Caco-2 cells, both by inducing acceleration of flagellar motility and increasing chemotaxis.